2011
DOI: 10.1007/s00125-011-2371-6
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes is associated with impairment of uterine contractility and high Caesarean section rate

Abstract: Aims/hypothesisThe prevalence of births worldwide complicated by diabetes mellitus is increasing. In the UK, for example, <25% of diabetic women have a non-instrumental vaginal delivery. Strikingly, more than half the Caesarean sections (CS) in these patients are non-elective, but the reasons for this are not understood. We have tested the hypothesis that poor myometrial contractility as a consequence of the disease contributes to this high CS rate.MethodsWe compared spontaneous, high K depolarisation and oxyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 45 publications
2
29
0
2
Order By: Relevance
“…This adds to previous in vitro studies showing contractility reflecting different clinical conditions, such as diabetes, obesity and postterm pregnancies [10], [26], [27]. Myometrium from twin pregnancies has contractions that are shorter but more frequent than myometrium from singleton pregnancies.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This adds to previous in vitro studies showing contractility reflecting different clinical conditions, such as diabetes, obesity and postterm pregnancies [10], [26], [27]. Myometrium from twin pregnancies has contractions that are shorter but more frequent than myometrium from singleton pregnancies.…”
Section: Discussionsupporting
confidence: 58%
“…Previous work from our group has shown that in vitro myometrial contractility can reflect in vivo clinical activity and labour outcome [10], [11]. The question therefore arises whether in vitro activity of myometrium from twins is different to that of singletons, making it a useful model for mechanistic studies focussed on risk of preterm labour.…”
Section: Introductionmentioning
confidence: 99%
“…However, published research from other investigators provides further explanation as to how these clinical factors may modify the biologic effect of oxytocin in various ways. Compared to non-diabetic women, diabetic women have reduced myometrial muscle mass and decreased calcium channel receptors and calcium signaling in their myometrial tissues [21]. While both the diagnosis of preeclampsia and magnesium use were more common among women who received oxytocin doses >20 mu/min in univariable analysis, only magnesium use was demonstrated to be independently associated with high oxytocin dose after controlling for confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, insulin can lead to muscle hypertrophy. Interestingly, diabetes has been associated with impairment of uterine contractility [18]. It is very likely that uterine hypertrophy in the adult Bscl2 −/− mice is the consequence of elevated glucose levels and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…We have been studying the functions of seipin in reproductive systems using seipin-deficient Bscl2 −/− mice and identified roles of seipin in mammary gland development, vaginal opening, and spermatogenesis [11,12]. Since seipin deficiency is associated with muscle hypertrophy and diabetes [10,17], diabetes has been associated with impairment of uterine contractility [18], and uterine smooth muscle contractions are critical for parturition, it was hypothesized that seipin deficiency might affect the myometrium to influence parturition. This hypothesis was tested in seipin-deficient Bscl2 −/− adult female mice.…”
Section: Introductionmentioning
confidence: 99%